The arsenal of democracy : FDR, Detroit, and an epic quest to arm an America at war - Baime, A. J. (Albert J.) (Houghton Mifflin Harcourt, 2014)
Tells the incredible story of how Detroit answered the call to arms during WWII, centering on Henry Ford and his tortured son Edsel, who, when asked if they could deliver 50,000 airplanes, made an outrageous claim: Ford Motor Company would erect a plant that could yield a "bomber an hour."